Cat got your killer - Ryan, Sofie, 1958- (Ryan, Sofie, 1958- Second Chance cat mystery, 2025)
"Sarah Grayson, secondhand store owner, and her clever rescue cat Elvis are right on the tail of a criminal... Summer is around the corner and Sarah is making sure the store is stocked and ready for tourist season. But while the weather's heating up, Sarah gets involved in a case that is decidedly cold, when a man who was linked to a drowning death years ago is found dead himself, on the same stretch of beach. Some of Sarah's friends from the store knew the victim--and the young woman who drowned--very well and are concerned they could be dragged into the case. It's beginning to look like an innocent man may be in prison and that drowning death might in fact be the work of a killer who has struck again. Between Charlotte's Angels, the group of senior citizen private detectives who operate out of the store, and Elvis's abilities to sniff out trouble, Sarah won't let a second chance at catching this purr-petrator pass her by."--Providedby publisher.